Pražské sídliště Solidarita – můj dům, můj domov: Studie přináležení k místu - Hodúlová, Tereza (Lidé města, 2019)
The aim of this article is to introduce the study of place attachment in the Solidarita Housing Estate, which was built as one of the first prefabricated housing estates in Prague between 1946 and 1951, in the period of post-war reconstruction in Czechoslovakia. Knowing more about people and their needs, wishes, and feelings developed in particular places (especially in their homes) is an important feature for knowing how to create cities, neighbourhoods, and places for them. One of the most important places for people is their home. In this study, based on the mixed use of qualitative methods (interviews, observation, mental mapping), I attempt to show how residents of the Solidarita Housing Estate in Prague perceive their homes. Building on the anthropological concept of place attachment (Altman & Low 1992) and its three-dimensional place-person-process framework (Scannell, & Gifford 2009), I want to discuss what the relationship to their home is and if this environment, which was established on cooperation, the ideal of social solidarity, and this human scale have an importance in this relationship.